Lithiation of WO3 films by evaporation method for all-solid-state electrochromic devices. (20th September 2020) - Li, Wenjie; Zhang, Xiang; Chen, Xi; Zhao, Yingming; Wang, Lebin; Chen, Mingjun; Li, Zitong; Zhao, Jiupeng; Li, Yao
Highlights: The effect of Li thickness on the optical properties of WO3 films was investigated. All-solid-state ECD with optimal Li thickness was prepared by evaporation method. The ECD showed large optical modulation 64.9% at 680 nm and 52.5% at 550 nm. High CE 106.6 cm 2 /C and superior cycle stability up to 4000 cycles were obtained. Abstract: Lithium (Li) electrolyte plays an important role in the electrochromic devices (ECDs), however, there are few studies on the matching between Li content and electrochromic layer in all-solid-state ECDs. In this work, lithiation WO3 films with different Li thickness were prepared by evaporation method to investigate the effect of Li thickness on the optical properties of WO3 films. Meanwhile, the Li storage capacity of WO3 in liquid electrolyte was calculated. The results showed that the optimal thickness of Li for 450 nm WO3 film prepared by evaporation was 42 nm. All-solid-state ECD glass/ITO/NiO/ZrO2 /Li/WO3 /ITO with optimal Li thickness exhibited large optical transmittance modulation (64.9% at 680 nm and 52.5% at 550 nm), high coloration efficiency (CE, 106.6 cm 2 /C at 550 nm) and superior cycle stability (98% retention of the maximum optical modulation after 4000 cycles). This work provides a new idea for the design and preparation of all-solid state ECDs. Graphical abstract: Image, graphical abstract